2023
DOI: 10.1021/acs.bioconjchem.2c00493
|View full text |Cite
|
Sign up to set email alerts
|

Bioderived Lipoic Acid-Based Dynamic Covalent Nanonetworks of Poly(disulfide)s: Enhanced Encapsulation Stability and Cancer Cell-Selective Delivery of Drugs

Abstract: Dynamic covalent poly(disulfide)-based cross-linked nanoaggregates, termed nanonetworks (NNs), endowed with pH- and redox-responsive degradation features have been fabricated for stable noncovalent encapsulation and triggered cargo release in a controlled fashion. A bioderived lipoic acid-based Gemini surfactant-like amphiphilic molecule was synthesized for the preparation of nanoaggregates. It self-assembles by a entropy-driven self-assembly process in aqueous milieu. To further stabilize the self-assembled n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 89 publications
1
10
0
Order By: Relevance
“…In addition, the LA-based cross-linkers have hydrophobic ends while M­(P)­A-based cross-linkers are hydrophilic end groups. This might result in the LA end groups forming a hydrophobic core around the hydrophilic PEG units, therefore shielding the effect of the hydrophilic ether groups. This agrees with the XRD data that reveal a difference in orientation of the crystal structure for LA- and M­(P)­A- based films.…”
Section: Resultssupporting
confidence: 81%
“…In addition, the LA-based cross-linkers have hydrophobic ends while M­(P)­A-based cross-linkers are hydrophilic end groups. This might result in the LA end groups forming a hydrophobic core around the hydrophilic PEG units, therefore shielding the effect of the hydrophilic ether groups. This agrees with the XRD data that reveal a difference in orientation of the crystal structure for LA- and M­(P)­A- based films.…”
Section: Resultssupporting
confidence: 81%
“…3c and d) showed that the nanonetwork has a slightly larger size compared to the nanoassemblies due to the formation of multiple covalent bonds of β-thioesters inside the core of the nanonetwork. 68,81 The guest loaded nanonetwork was found to be even larger than that of the empty nanonetwork as probed by the DLS experiment. This could be attributed to the enlargement of the nanonetwork to make more room inside the core for the guest molecules (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…However, the strategy of covalently crosslinking the core to stabilize the small molecule based nanoaggregates has shown excellent potential in the stabilization of loaded drugs and controlled release as previously reported by us and a few groups. 44,49,[66][67][68][69] To this end, we aimed to fabricate robust nanoassemblies with high stability in the vascular system and the capability of quantitative reproducibility of the building block for delivering drugs to the desired locations without leakage in the circulation pathway for successful clinical evaluation. Here we proposed the fabrication of dual pH responsive β-thioester based cross-linked nanoassemblies termed nanonetworks (NNs) from a very simple small molecular amphiphile, integrated with a tertiary amine moiety.…”
Section: Introductionmentioning
confidence: 99%
“…The DLS experiment accomplished with palladium(II) complex R-[3] and the substrates in toluene showed the presence of nanoaggregates with an average diameter of 190.62 nm, whereas the DSL data with the reaction mixture containing active pre-catalyst R-[4] showed an average particle diameter of 0.83 nm. [22] It is believed that the inactive nature of the complex R-[3] in the αarylation of 1-methyl-2-oxindole is due to the alteration of the molecular complex to palladium nanoparticles (PdÀ NPs). A black color precipitate was observed when the reaction mixture was heated in the presence of complex R-[3], which is possibly due to the PdÀ NPs (see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The dynamic light scattering (DLS) measurement has also been conducted to indicate the formation of the Pd−NPs in the reaction mixture containing R ‐[ 3 ] (Figure 3). The DLS experiment accomplished with palladium(II) complex R ‐[ 3 ] and the substrates in toluene showed the presence of nanoaggregates with an average diameter of 190.62 nm, whereas the DSL data with the reaction mixture containing active pre‐catalyst R ‐[ 4 ] showed an average particle diameter of 0.83 nm [22] . It is believed that the inactive nature of the complex R ‐[ 3 ] in the α ‐arylation of 1‐methyl‐2‐oxindole is due to the alteration of the molecular complex to palladium nanoparticles (Pd−NPs).…”
Section: Resultsmentioning
confidence: 99%